Impact of co-morbidities on survival after heart transplant in females of childbearing age: analysis of the International Society for Heart and Lung Transplantation (ISHLT) Registry. (3rd October 2022) - Bhagra, C J; Cherikh, W S; De Filippis, E M; Ross, H; Stehlik, J; Macera, F
Abstract: Background: Data on life expectancy specific to female heart transplant (HT) recipients of reproductive age are lacking, but are needed to inform shared decision making at the time of pre-conception counseling. We analyzed the ISHLT registry for post-transplant survival and studied the impact of co-morbidities in women of childbearing age. Methods: Female HT recipients reported to the ISHLT registry who were aged 15–45 yrs at time of HT were included in this retrospective analysis. Primary outcome was post-transplant survival. Secondary outcomes included the impact of co-morbidities on conditional survival at 5, 10 and 15 years. Results: Of 121, 501 HT recipients (Jan 1992–June 2018), 30, 179 (24.8%) were women. 9, 229 (7.6%) were 15–45 yrs at time of HT. Overall median post-transplant survival was 15.2 yrs. Diabetes mellitus (DM) and/or severe chronic kidney disease (CKD) at HT adversely impacted long-term survival (Figure 1). Co-morbidities including cardiac allograft vasculopathy (CAV), DM and CKD negatively impacted 5yr and 10yr conditional survival, individually as well as a combination (Figure 2). 15yr conditional survival confirmed the negative impact of DM and CKD, while CAV did not reach statistical significance. Conclusion: Female HT recipients of childbearing age have favorable survival post-HT. Conditional survival at 5 and 10 yrs is negatively impacted by CAV, DM and CKD. The quantification of survival outcomes after heart transplant in women of childbearing age may improve counseling as part of pre-conception informed decision making. Funding Acknowledgement: Type of funding sources: None.